2014
DOI: 10.1073/pnas.1323606111
|View full text |Cite
|
Sign up to set email alerts
|

Improving management of small natural features on private lands by negotiating the science–policy boundary for Maine vernal pools

Abstract: Vernal pools are far more important for providing ecosystem services than one would predict based on their small size. However, prevailing resource-management strategies are not effectively conserving pools and other small natural features on private lands. Solutions are complicated by tensions between private property and societal rights, uncertainties over resource location and function, diverse stakeholders, and fragmented regulatory authority. The development and testing of new conservation approaches that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Most policies relating to frog conservation focus on immediate habitats surrounding breeding habitats (Calhoun et al, 2014;Semlitsch, 2000). However, our study revealed that decreasing forest cover (at different spatial scales) and increasing road cover within 1 km of ponds reduces the occurrence of infrequently encountered frog species.…”
Section: Amphibian Conservation In Urbanizing Landscapesmentioning
confidence: 68%
See 1 more Smart Citation
“…Most policies relating to frog conservation focus on immediate habitats surrounding breeding habitats (Calhoun et al, 2014;Semlitsch, 2000). However, our study revealed that decreasing forest cover (at different spatial scales) and increasing road cover within 1 km of ponds reduces the occurrence of infrequently encountered frog species.…”
Section: Amphibian Conservation In Urbanizing Landscapesmentioning
confidence: 68%
“…However, our ability to guide conservation efforts remains limited because amphibians are among the least studied vertebrate groups in urbanizing landscapes (McDonnell & Hahs, 2008). Although the number of studies of amphibians in urban areas and in landscapes under urban development is growing, planners and managers still lack information to effectively guide amphibian conservation in most urbanizing landscapes worldwide (but see Calhoun, Jansujwicz, Bell, & Hunter, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given these social and ecological characteristics, scientists and regulators identified the desired goal of maintaining or creating landscapes with interconnected vernal pool complexes; human communities that understand and appreciate the multiple ecosystem services and values associated with vernal pools; and conservation policies and strategies that preserve private property rights and economic development opportunities (Calhoun et al 2014). Collaborators also identified how maintaining or achieving these goals is threatened by stressors such as rapid and largely unplanned landscape development; policies that do not adequately regulate vernal pools as interconnected ecosystems; and relatively unknown changes related to climate, invasive species, and demographic shifts (Kneitel 2014,Tuytens et al 2014).…”
Section: Ses Resilience Goal: Maintaining Healthy Vernal Pools and Humentioning
confidence: 99%
“…Although the citizen science program provided useful data, the 2007 regulation was still highly controversial (Calhoun et al 2014). Following passage of the vernal pool regulation, a second citizen science program, the Vernal Pool Mapping and Assessment Program (VPMAP), was launched in 12 Maine towns as a response to the regulatory controversy.…”
Section: Citizen Science Approach To Resiliencementioning
confidence: 99%
See 1 more Smart Citation